A Case Of Congenital Parvovirus B19 Infection Diagnosed Through Placenta - Nur Syahrina Rahim; Siti Khadijah Mohd Fuad; Charnjeet Kaur Parthamam Singh; Khairul Anuar Zainun; Abdul Rahman Hayati (College of Pathologist, AMM, 2024)
Conference: The International Congress of Pathology & Laboratory Medicine 2018: Frontiers in Diagnostic Pathology